PEDIATRIC INGUINAL HERNIA IN BASRAH - Sadik H Kadhem; Haithem H Ali; Haider A Jassim (Basrah Journal of Surgery, 2015)
Abstract Inguinal hernia repair is one of the most frequently performed surgical procedure in pediatric patients. An inguinal hernia does not resolve spontaneously and must be repaired because of high risk of complications. The aim of this study is to determine epidemiologic index and complications of inguinal hernia in pediatric patients. This retrospective study was carried out in the Basrah Children Hospital. All patients who underwent surgeries for inguinal hernia from 2012 to 2014 were included in this study. Their hospital records were reviewed for age, sex, side of the hernia, presentation, wound infection, recurrence, and other complications. In this study, 877 children were included. 766 (87.3%) were boys and 111 (12.7%) were girls. Most common age of presentation is between 6 months to 6 years which compromise 54.6%. Right-side and left-side inguinal hernia was observed in 531 (60.5%) and 276 (31.5%) cases, respectively. Bilateral inguinal hernia was observed in 70 (8%) cases. One hundred forty eight (16.9%) children presented as emergencies with irreducible hernia. Emergency presentation was more in male gender and more in the first 6 months of life. Postoperative complication rate for elective was 3.2% and for emergency groups was 51.7%. In conclusion, most of the hernias involved male patients. Postoperative complications were observed in 51.7% of the emergency cases, so inguinal hernia in children should be operated as early as possible to avoid incarceration and to decrease post-operative complications.